Virtual tutoring - Marcos, Adérito (2020)
The project VIRTUAL TUTORING – the virtual tutor as learning mediating artifact in online university education, is an ongoing project, with the main goal of analyzing the pedagogic impact of an anthropomorphic user interface on a typical distance learning environment targeted to support online higher education. This demands the creation of animated avatars for virtual tutors, able to display intelligent behaviour while interacting with the students. A Virtual Tutor should be analogous to a real human one, being able to proactively understand, solve and intervene in different student learning situations. This paper gives an overview of the project present development status.